Tracking system performance for the proposed SHADOWS experiment at CERN - Roy, Shreya (Nuclear instruments & methods in physics research. Section A, Accelerators, spectrometers, detectors and associated equipment, 2024)
The proposed SHADOWS experiment, Search for Hidden And Dark Objects With the SPS, is a proton beam-dump experiment at the CERN SPS. Positioned off-axis to suppress background, SHADOWS can profit from the high intensity ECN3 proton beam line, to explore the existence of a wide range of feebly-interacting particles (FIPs). The detector, with dimensions of 2.5 × 2.5 m2 and a length of 34 m, is designed for optimal tracking and timing performance, facilitating the identification and reconstruction of various visible final states of FIP decays. Despite the excellent outcome of the CERN SPS Committee review, the CERN Research Board decided to stop the project in March 2024. In this article we present the tracking system performance study based on simulation as presented in the Proposal. We show that using straw drift-tubes of 1 cm diameter, we can achieve a few mm vertex resolution and 1% mass resolution.
Online verfügbar: 1. Oktober 2024, Artikelversion: 7. Oktober 2024
Gesehen am 25.03.2025